Serving Soft Power and Public Diplomacy with Chinese Characteristics : A Communication Analysis of the Confucius Institute at the University of Nairobi - (:unkn) unknown (My University, 2020)
The age-old link and “socialist friendships” between China and various African states have enjoyed a privileged position in Beijing’s foreign policy since the proclamation of the People’s Republic of China in 1949. As a “proving ground” of China’s soft power and an exceptional place to project the “Chinese Dream”, Africa has become a valuable target of Beijing’s socialist development model. China weaves relationships with African populations through intense public diplomacy. Such practice revolves around its promise to sustain economic growth and to improve the daily lives of people in Africa. The Confucius Institute is currently a flagship brand of China’s statecraft in Africa through which Beijing advances its reputation among local publics. Beyond its pedagogical and cultural missions, the Confucius Institute is an effective but subtle spokesperson for Beijing. Within its local branches, trained employees actively participate in a long-term strategy of influence based on affective engagement. They engage local students in numerous group activities and build strong bonds with them. Their voices are individual, but their homogenous discourse resonate with “China’s voice” to deliver formulated Communist Party of China’s propaganda to foreign publics. In doing so, these teachers wield China’s soft power. The aim of this Ph.D. dissertation is to examine public diplomacy with Chinese characteristics, its conceptualization, institutionalization, and practices. From a communication perspective, this study is an exploration of the hybrid and complex nature of China’s public diplomacy, which Beijing has strategically organized to deploy its soft power in Africa.Ethnographic observation in Nairobi, Beijing, and Shanghai shed light on the strategic communication practices associated with the Confucius Institute. By mobilizing institutional discourse and media discourse studies and conducting semi-structured interviews, I invest
Keywords: African Research